YOKES OF THE HOLY-ONES: THE EMBODIMENT OF A CHRISTIAN VOCATION - Koltun-Fromm, Naomi (Harvard theological review, 2001)
In his sixth demonstration, Aphrahat, the fourth-century Persian Christian sage, describes the behavior of the bnay qyama, the “members of the covenant,” through the image of the “yoke of the holy-ones.” These men, often called, ihidaye, “single-ones,” or “single-minded-ones,” are a celibate elite. The ihidaye's sexual status separates them psychologically and physically from the rest of the Christian community.While some scholars, including Jean Parisot (Patrologia Syriaca 1.240) have translated ihidaya as “monk,” Parisot goes so far as to render the title of the sixth demonstration, “Concerning the ihidaya,” as “De Monachis.” John Gwyn (NPNF, Sec. ser., 13.362) follows suit with “Of Monks.” This translation is anachronistic at best as Arthur Vööbus has pointed out (The History of Asceticism in the Syrian Orient 1 [Louvain: CSCO 184, 1958] 106, 220). Even if in later generations the single ones became associated with the monastic movement, these early celibates were not monastic. They continued to live and function within their communities. Yet the sexual behavior of these men is more than a lifestyle choice; it is a religious vocation of sexual continence embodied in the name they bear, “single-ones,” as well as the “holy-yoke” they wear.